Rate of temperature reduction at cryopreservation primordial germ cells (PGC) of three Indonesian native chicken. - Tatan Kostaman; S. Sopiyana; A.R. Setioko (Jurnal Ilmu Ternak dan Veteriner, 2011)
Primordial germ cells (PGCs) are original cells of spermatogonia in the testes or oogonia in the ovary. PGCs in poultry can be harvested and stored in the liquid nitrogen and can be used for conservation as genetic materials of poultry. The objective of this study was to obtain the optimal rate of temperature reduction on PGCs quality from three different Indonesian native chicken after thawing. Fertile eggs obtained from native chicken were incubated for 56 hours to obtain embryo at stage of 14-16. PGCs were isolated from the blood using modified Nycodenz Gradient Centrifugation technique. There after they were kept in a straw and equilibrated for 15 minutes at 5oC and frozen at the rate of temperature reduction of 0.3, 0.5, and 1oC per minute using embryo freezing machine (FHK Fujihara: ET-1). After the temperature reached -30oC, then they were plunged directly into the liquid nitrogen. Recovery rate and viability of PGCs after freezing and thawing were measured. The results of this study showed that the average recovery rate of PGCs that have been frozen at rate of temperature reduction of 1, 0.5, and 0.3oC per minute were 35.6, 43.9, and 44.9% respectively. However the rate of temperature reduction of 0.5 and 0.3oC per minute did not significantly affect the recovery rate. The average percentage of viability of PGCs that were frozen at the rate of 1, 0.5 and 0.3oC per minute were respectively 62.6, 77.5, and 77.4%. It seems that the viability followed the trend of recovery rates where the 1oC per minute reduction was the lowest quality compared to the other two treatments. It is concluded that the reduction of 0.5 or 0.3oC per minute are considered as the ideal temperature reduction when native chicken PGCs are frozen. Key Words: PGCs, Native Chicken, Conservation